Proceedings of the international forum on water resources management and irrigation modernization in shanxi province, China (Food and Agriculture Oranization of the United Nations, 2006)
Opening session, plenary presentations, opening for strategic and policy innovations at the river basin level, options for technical and managerial improvements at the system and level.